(untitled) (Jurnal Bahasa, 2007)
In Malay, a spreading of glide occurs in root and a.!Jix boundaries (prefix boundary and sujfix boundary) "Vhen a first vowel of vowel sequences is a high vowel such as in the words lbuahl [buwah], /diam/ [diyam], lburu + an/ [buruwan] and /tari + an/ [tariyan). However, a default process of glottal stop insertion does not occur in roots but it occurs in affix boundaries and morphological word boundaries (reduplicated words, compound and sy ntactic phrases) such as in the words /guna + an/ [guna?an], /mula + i! [mula?i], /di + ambil/ [di?ambel], /anai-anai/ [anai?anai] and /satia + usaha/ [s tiya?usaha]. On account of glottal stop does not occur in roots but only occurs in morphological word, therefore it is so-called a post lexical process.